Towards Elderly Well-Being: A Comprehensive Overview Geriatric Health Service as an Answer to Demographic Challenges in India - Gautam Makwana; H Elizabeth (Smart Society, 2023)
India is undergoing a significant demographic transition, with declining birth rates and increasing life expectancy contributing to a rapidly growing elderly population. By 2050, the number of older adults is projected to quadruple, placing immense pressure on the country’s healthcare infrastructure. A recent World Health Organization report highlights that the rising elderly population in India and China will further strain national health systems. Despite this, geriatrics remains an underdeveloped field in Indian medical education, resulting in a lack of specialized healthcare services for older adults. This study provides an overview of India’s geriatric healthcare system, focusing on existing policies, infrastructure, and healthcare models. Through a comprehensive review of healthcare programs, government initiatives, and geriatric service frameworks, this study identifies key challenges such as inadequate specialized training, limited healthcare accessibility, and disparities in service quality, particularly in rural areas. Additionally, this study examines the unique healthcare needs of older adults, including frailty, atypical disease presentations, and increased risks of complications. The findings highlight the urgent need for a more integrated and multidisciplinary approach to geriatric care. Strengthening primary healthcare services, increasing geriatric training for healthcare professionals, and promoting community-based care models are crucial steps in addressing these challenges. Raising awareness of the medical and socioeconomic difficulties faced by India’s elderly population is essential to improving their quality of life. By enhancing existing healthcare policies and infrastructure, India can better prepare to meet the needs of its ageing population and ensure sustainable elderly care services in the future.